Repercussões maternas de ratas vacinadas com proteína peroxidoxina recombinante de Leishmania braziliensis durante a prenhez - Souza, Rafaianne Queiroz de Moraes (2015)
Leishmaniasis considered antropozoonoses have worldwide distribution and has become a serious public health problem. Science seeks new methods of prevention and control of this disease, including research for safe and effective vaccines. The recombinant protein peroxidoxin of Leishmania braziliensis conjugated to the adjuvant Monophosphoryl Lipid (MPL) has been shown to be a promising candidate vaccine antileishmaniose. However, there are no reports of studies that confirm it is safety during pregnancy. Therefore the aim of the present study was to evaluate the effect of protein peroxidoxin of Leishmania braziliensis conjugated with MPL on the reproductive outcomes administered to rats during pregnancy. For this study, female Wistar rats were mated and randomized in three groups: Control- composed of pregnant rats treated with saline; Adjuvant - composed of pregnant rats treated with adjuvant MPL (Monophosphoryl Lipid A) and Vaccine - rats that received injection with adjuvant associated with protein recombinant peroxidoxin. The administration occurred by subcutaneous injection in the dorsal region, in 3 time (day 0, 7, 14 of pregnancy). The Body weight, feed intake and water were measured weekly. At day 21 of pregnancy, all rats were anesthetized and killed. Blood samples were collected to investigate the he production of specific antibodies and transfer of immunity by ELISA (Enzyme Linked Immuno Sorbent Assay), biochemistry and leukocytes analysis. Heart, liver and kidneys were weighed. The gravid uterus was removed to obtain reproductive performance data. The data showed that the IgG immunoglobulin was higher in the vaccine group compared with control and adjuvant group, the values were (p>0.05). There was no statistical difference between the groups in relation to body weight, water and food intake, organ weights, biochemical and blood leukocytes. The postimplantation loss increased in vaccine group (14.7%), control group was (5,0)% and adjuvant group was (4.4%). Others reproductive outcomes have not changed. These findings support that the immunization stimulated the production of IgG immunoglobulin also not showed maternal toxicity, but increase the postimplantation loss, demonstrate that use during pregnancy requires caution.